PERAN MANAJEMEN PENJAMINAN MUTU INTERNAL AKADEMIK UNTUK MEWUJUDKAN MOTIVASI PRESTASI MAHASISWA : PERAN MANAJEMEN PENJAMINAN MUTU INTERNAL AKADEMIK UNTUK MEWUJUDKAN MOTIVASI PRESTASI MAHASISWA - AGOES DARIYO; Ade Surya Wijaya; Raja O. Tumanggor; Ayi N. Hidayat; Ratnawulan (UHN IGB Sugriwa Denpasar, 2023)
Research on achievement motivation in the context of academic internal quality assurance management is rarely carried out by educational experts or educational psychologists. Encouraged to know this phenomenon, the researchers tried to realize the research topic by using a quantitative approach. Data collection techniques with interviews, observations and documentary records. Interviews were conducted with heads of faculty educational institutions, lecturers, and students. Observations were made of the process of learning activities in educational settings. Documentation records were obtained from the documentation recording section in each educational institution. The location of the research was at Tarumanagara University, Jakarta and the YPIB Majalengka Nursing Academy, West Java. Data analysis using a thematic approach. The results found that (a) internal academic quality assurance management is able to create achievement motivation in students, (b) internal academic quality assurance management is able to create a positive class climate that is imposed by students, (c), Furthermore, both achievement motivation and class climate can help students achieve good learning achievement.